Anthropomorphizing Nature as a Tool for Environmental Education. Opinions of Pedagogy Students in the Context of Represented Environmental Ethics - Agnieszka Kozłowska; Małgorzata Czapla (Studia Ecologiae et Bioethicae)
The purpose of the study was to check pedagogy students’ opinions on using anthropomorphizing nature for the development of pro-environmental knowledge and behaviour in the context of their own environmental ethics orientations.  An online survey for university pedagogy students from Poznan, Poland, was conducted. N=221 respondents, of whom 97% were women, filled out the questionnaires. Descriptive statistics were used for closed questions on students’ opinions about using anthropomorphizing nature for environmental education. To find out the respondents’ environmental ethics orientations, content analysis of answers to open questions was used, applying theory-based categories of environmental orientations derived from environmental ethics (anthropocentrism, biocentrism). The findings revealed that the majority of students believe that anthropomorphism of nature helps in the development of pro-environmental behaviour (62.4%) and knowledge (55.8%). In justification, most (63.8%) presented anthropocentric attitudes; 27.5% of answers were biocentric, and 8.8% - mixed eclectic. According to the other questions the respondents supported biocentric environmental norms. Their justifications, however, again revealed mostly anthropocentric motivations 63.2%. Conclusion: Pedagogy students, although they support biocentric norms, believe that anthropomorphism of nature will be the right tool for environmental education, and use anthropocentric arguments in their justifications. In their future pedagogical practice, they will rather develop anthropocentric orientations in children, building positive attitudes towards nature on (false) belief in similarities of human and non-human living organisms, instead of recognition of their “otherness” and intrinsic value.